TREATMENT OF PATIENTS WITH PEPTIK ULCER OF THE STOMACH AND DUODENUM IN A POLYCLINIC - PhD, Associate Professor A.F. Rakhimov; DSc M.E. Eshbekov (Scholar Express Journals, 2026)
In the article "Treatment of patients with peptic ulcer of the stomach and duodenum in a polyclinic" reports on the results of outpatient treatment of patients with peptic ulcer using the original method proposed by them - endoscopic autohemoapplication (EAGA) of ulcers.
Keywords: peptic ulcer disease; endoscopic autohemoapplication of ulcers; outpatient treatment